2019
DOI: 10.1590/2175-8239-jbn-2018-0086
|View full text |Cite
|
Sign up to set email alerts
|

Montreal Cognitive Assessment for cognitive assessment in chronic kidney disease: a systematic review

Abstract: Introduction: There is evidence in the literature that cognitive impairment is more prevalent in individuals with chronic kidney disease (CKD) than in the general population. The Montreal Cognitive Assessment (MoCA) is an instrument with a good application profile for cognitive evaluation of patients with CKD-like impairments. The objective of this study is to perform a systematic review of MoCA use in the context of CKD. Method: The keywords "Montreal Cognitive Assessment", "Kidney Disease" and "Chronic Kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
(54 reference statements)
0
10
0
6
Order By: Relevance
“…The Montreal Cognitive Assessment (MoCA; Nasreddine et al, 2005), an extensively validated screening and clinical assessment tool in CKD (Amatneeks & Hamdan, 2019), was used to assess participants for cognitive impairment. The MoCA is a one page, 30‐point test that assesses several cognitive domains including executive function, visuospatial function, complex attention, language, memory recall and abstract thinking.…”
Section: Methodsmentioning
confidence: 99%
“…The Montreal Cognitive Assessment (MoCA; Nasreddine et al, 2005), an extensively validated screening and clinical assessment tool in CKD (Amatneeks & Hamdan, 2019), was used to assess participants for cognitive impairment. The MoCA is a one page, 30‐point test that assesses several cognitive domains including executive function, visuospatial function, complex attention, language, memory recall and abstract thinking.…”
Section: Methodsmentioning
confidence: 99%
“…Despite using a medical interpreter, the language component of MoCA may be representative of patients’ lack of comprehension due to language barriers rather than cognitive impairment. Translations of MoCA from English to other languages are feasible and effective; however, the cutoff values of MoCA scores for screening cognitive deficiencies vary based on language in other disease processes 42–49 . Therefore, despite using a medical translator, a limitation of this study is the effect of the language barrier on using MoCA.…”
Section: Discussionmentioning
confidence: 95%
“…20 This study demonstrated no association between for screening cognitive deficiencies vary based on language in other disease processes. [42][43][44][45][46][47][48][49] Therefore, despite using a medical translator, a limitation of this study is the effect of the language barrier on using MoCA. ESL is a compounding factor for failing MoCA, which unfortunately renders MoCA as an ineffective tool to appropriately differentiate patients with frailty and genuine cognitive decline versus patients with a language barrier.…”
Section: Discussionmentioning
confidence: 98%
“…These could limit the generalizability and comparability of similar studies. Some studies [ 80 , 81 ] indicated that the Montreal Cognitive Assessment (MoCA) showed better utility as a tool for assessing patients with CKD. Third, we did not assess severe cardiovascular diseases or other neurological disorders in our study.…”
Section: Discussionmentioning
confidence: 99%